Ensuring an operational equity-based global stocktake under the Paris Agreement - Hesham Al-Zahrani; Qimin Chai; Sha Fu; Yaw Osafo; Adriano Santhiago de Oliveira; Anushree Tripathi; Harald E. Winkler; Vicente Paolo B. Yu (South Centre, 2019)
One of the key provisions of the Paris Agreement that was adopted in December 2015 at the 21st session of the Conference of the Parties to the United Nations Framework Convention on Climate Change is Article 14 on the global stocktake (GST). The GST is intended to be the mechanism by which the Convention Parties that are Parties to the Paris Agreement would be able to periodically take stock of the implementation of the Paris Agreement and to assess collective progress towards achieving the purpose of the Agreement and its long-term goals. This research paper discusses how equity as a principle and a concept played a key role in shaping the modalities for the GST, and looks in detail at the operational modalities for the GST that were agreed upon in Katowice in December 2018 in relation to how equity should be considered and made operational.
Keywords: 300; Klimawandel; Internationale Umweltpolitik; Welt